Penatalaksanaan impaksi gigi kaninus rahang atas Management of impacted maxillary canine - Anita Septiyani; M. Hendra Chandha; Muhammad Ruslin (DiscoverSys Inc., 2012)
Impacted canines can be detected in early age. The clinicians might be able to prevent them by means of properclinical diagnosis, radiographic evaluation and timely interceptive treatment. Various surgical and orthodontictechniques can be used to recover impacted maxillary canines. Surgical technique used to manage impacted caninesincluding gingivectomy, apically positional flap, and closed eruption technique. The aim of this review is to providethe management of impacted maxillary canines. Combination between surgical and orthodontic techniques are theeffective method to manage impacted maxillary canines with good result.